Chemical looping gasification of rice husk to produce hydrogen-rich syngas under different oxygen carrier preparation methods. (16th October 2020) - Huang, Xiangneng; Hu, Zhifeng; Miao, Zhenwu; Jiang, Enchen; Ma, Xiaoqian
Abstract: The chemical looping gasification (CLG) of rice husk was conducted in a small fixed-bed reactor to investigate the effects of oxygen carrier preparation methods, active components, Fe loadings, water inflow and successive redox cycles. The gas content, the relative gas concentration, lower heating value of syngas (LHV), carbon conversion efficiency, gasification efficiency, H2 -TPR, XRD, BET and SEM were analyzed to obtain CLG reaction characterization and comprehensive performance of oxygen carrier. The results showed that compared with several methods and active components, the coprecipitation method with a Fe:Al ratio of 2 was the best preparation method for oxygen carrier. Furthermore, the H2 concentration was 57.29%, while the gasification efficiency and carbon conversion efficiency were 95.79% and 51.56%. Meanwhile, the oxygen carrier prepared by coprecipitation had a greater performance of oxygen release and reduction. There was an optimal water inflow to obtain the highest gas content, carbon conversion efficiency and gasification efficiency. Thereinto, the H2 concentration was stable at 54.07–57.65%. And the highest gas content of 78.33% and carbon conversion efficiency of 54.42% were obtained at a water inflow of 14.0 mL/h, while the highest gasification efficiency of 95.79% was obtained at 16.8 mL/h. In addition, after ten successive redox cycles, the gasification performance, crystal size, specific surface area and pore structure were relatively stable. Moreover, the material composition remained basically unchanged. Highlights: Coprecipitation is the best preparation method to gain the highest H2 concentration. Fe is the optimal active component to gain a highest H2 concentration and efficiency. Al:Fe of 2:1 is the best Fe loading in oxygen carrier for a great performance. Water inflow is beneficial to increase the H2 concentration. Reaction performance and structure are stable after ten successive redox cycles.